2005
DOI: 10.1271/bbb.69.1970
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Dietary Calcium/Phosphorus Ratio Reduces Bone Mass and Strength in Ovariectomized Rats Enhancing Bone Turnover

Abstract: To clarify the effects of the dietary calcium (Ca)/phosphorus (P) ratio on bone mineralization under the condition of estrogen deficiency, Wistar strain female rats were ovariectomized (OVX) at 12 weeks old. At 16 weeks old, the rats were divided into three dietary groups fed varying levels of P containing 0.5% Ca: 0.25% P, Ca/P = 2; 0.5% P, Ca/P = 1; and 1.0% P, Ca/P = 0.5 respectively. This study indicates that the reduction of the dietary Ca/P ratio impairs trabecular bone turnover accompanying the accelera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…The present study indicated that HP intake additively decreased BMD in the absence of estrogen through stimulating bone resorption activity. Koshihara et al 5 reported that HP intake reduced BMD by increasing bone turnover in OVX rats, which is consistent with our results.…”
Section: Discussionsupporting
confidence: 93%
“…The present study indicated that HP intake additively decreased BMD in the absence of estrogen through stimulating bone resorption activity. Koshihara et al 5 reported that HP intake reduced BMD by increasing bone turnover in OVX rats, which is consistent with our results.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have indicated that estrogen deficiency induced by ovariectomy in female rats leads to an increase in Ca/P ratios in both tibial and femoral bones. The Ca/P ratio observed in ovariectomized rats is >2.0, whereas healthy female rats show values <2.0 [44][45][46]. Ca/P ratio increment in rats that underwent ovariectomy suggests a negative effect on the balance between bone resorption and bone formation activity [43].…”
Section: Discussionmentioning
confidence: 99%
“…Ca, Mg and P are known as major minerals for bone formation and bone mineralization (Koshihara et al, 2005). We analyzed Ca, Mg and P concentration in tissues, such as liver, muscle, kidney, SI and WAT in rats (ZA, PF and ZD).…”
Section: Discussionmentioning
confidence: 99%